Museo Marugame Hirai : Arte Español Contemporáneo. - Museo Marugame Hirai, Marugame (Marugame : Museo Marugame Hirai, 1993)
Barceló, Miquel ; Leiro, Francisco ; Perejaume ; Badiola, Txomin ; Risueño, Joaquin ; Urzay, Dario ; Berlin, Dis ; Moreno, Felicidad ; Cano, Eugenio ; Rojas, Antonio ; Irazu, Pello ; Cotanda, Ricardo ; Murado, Antonio ; Galindo, Jorge ; Abad, Antonio ; Espaliu, Pepe ; etc.
boek
Keywords: Spanje